Perfil bioquímico sérico de jabutis Chelonoidis Carbonaria (Reptilia, Testudinidae) mantidos em cativeiro - Pereira, Paulo Vinícius Rocha (2015)
Considered the testudine that has been most kept in captivity as a pet due to its extensive illegal trade, Chelonoidis carbonaria species (tortoise-piranga or red-leg-tortoise) is widely distributed in South America and Brazil . The objective was to measure the changes in protein compounds, metabolites, minerals, electrolytes and serum enzyme in Chelonoidis carbonaria held captive using analytical methods routinely used in clinical laboratories, as this dosages are laboratory tests used in veterinary medical clinic for the important contribution that provide diagnosis and prognosis of metabolic changes that affect these animals. For this, used were 25 specimens from C. Carbonaria. Was performed on each animal both sexes, Blood collection Serum for subsequent biochemical analysis. Analyses were processed in automatic analyzer (Flexor XL). It was observed that the results of the serum biochemical constituents C. carbonaria evaluated to show no significant differences in mean observed for other species Testudines, the differences being observed probably due to the difference managements, diet and normal physiological variations different species. There were no significant differences between males and females for the studied parameters and the values obtained for glucose levels in venous blood obtained by enzymatic colorimetric method (GVE) and digital glucometer (GVG). Analytical techniques routinely employed for biochemical tests appear to be suitable for determining the biochemical profiles of these animals with the exception of gamma glutamyltransferase (GGT) and creatine kinase enzyme (CK) and creatine kinase MB (CK-MB) showed wide variations of standard deviations. The results of this study can contribute to the interpretation of biochemical parameters of tortoises as well as support other studies that seek to reference values for the species.